Sex and Age Don't Matter, but Breed Type Does—Factors Influencing Eye Wrinkle Expression in Horses - Schanz, Lisa; Krueger, Konstanze; Hintze, Sara (Frontiers in Veterinary Science, 2019)
Identifying valid indicators to assess animals’ emotional states is a critical objective of animal welfare science. In horses, eye wrinkles above the eyeball have been shown to be affected by pain and other emotional states. From other species we know that individual characteristics, e.g. age in humans, affect facial wrinkles, but it has not yet been investigated whether eye wrinkle expression in horses is systematically affected by such characteristics. Therefore, the aim of this study was to assess how age, sex, breed type, body condition and coat colour affect the expression and/or the assessment of eye wrinkles in horses. To this end, we adapted the eye wrinkle assessment scale from Hintze et al. (2016) and assessed eye wrinkle expression in pictures taken from the left and the right eye of 181 horses in a presumably neutral situation, using five outcome measures: a qualitative first impression reflecting how worried the horse is perceived by humans, the extent to which the brow is raised, the number of wrinkles, their markedness and the angle between a line through both corners of the eye and the topmost wrinkle. All measures could be assessed highly reliable with respect to intra- and inter-observer agreement. Breed type affected the width of the angle (F2, 114 = 8.20, p < 0.001), with thoroughbreds having the narrowest angle (M = 23.80, SD = 1.60), followed by warmbloods (M = 28.00, SD = 0.60), and coldbloods (M = 31.00, SD = 0.90). None of the other characteristics affected any of the outcome measures, and eye wrinkle expression did not differ between the left and the right eye area (all p-values > 0.05). In conclusion, horses’ eye wrinkle expression and its assessment in neutral situations was not systematically affected by the investigated characteristics, except for ‘breed type’, which accounted for some variation in ‘angle’; how much eye wrinkle expression is affected by emotion or perhaps mood needs further investigation and validation.